2019
DOI: 10.1111/petr.13611
|View full text |Cite
|
Sign up to set email alerts
|

Preformed and de novo DSA are associated with T‐cell–mediated rejection in pediatric liver transplant recipients requiring clinically indicated liver biopsy

Abstract: Despite growing interest about the impact of donor‐specific HLA antibodies (DSA) in LT limited data are available for pediatric recipients. Our aim was to perform a retrospective single‐center chart review of children (0‐16 years) having undergone LT between January 1, 2005 and December 31, 2017, to characterize DSA, to identify factors associated with the development of de novo DSA, and to analyze potential associations with the diagnosis of TCMR. Information on patient‐ and donor‐characteristics and LB repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Of these, 37 (47.2%) showed a maximum DSA-MFI > 20,000 ( 20 ). In addition, de novo DSAs were detected in 60.3%–63% of pediatric LT patients ( 23 , 24 ). In LDLT, 32% of pediatric patients were found to have class II DSA post-transplantation ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 37 (47.2%) showed a maximum DSA-MFI > 20,000 ( 20 ). In addition, de novo DSAs were detected in 60.3%–63% of pediatric LT patients ( 23 , 24 ). In LDLT, 32% of pediatric patients were found to have class II DSA post-transplantation ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, severe TCMR in itself may be associated with elevated DSAs and C4d positivity, as can severe plasma cell-rich rejection. [27][28][29] Conventional immunosuppressive treatment of these cases may decrease C4d positivity and DSA titre, thus making the formal diagnosis of AMR more difficult to establish.…”
Section: Key Pointmentioning
confidence: 99%
“…With the minimization of immunosuppressants, it is often observed that liver transplant recipients also developed dnDSA in serum, with the tendency of this belonging to class II rather than class I [25,32]. In terms of the relation between dnDSA and TCMR, the prevalence of dnDSA was clearly higher in recipients who experienced TCMR, albeit without a correlation with frequency and severity [33]. With regard to the effects of dnDSA development, the correlation between dnDSA and more severe fibrosis was observed [34,35].…”
Section: Liver Transplantationmentioning
confidence: 99%